Glucocerebrosidase deficiency leads to neuropathology via cellular immune activation. - Evelyn S Vincow; Ruth E Thomas; Gillian Milstein; Gautam Pareek; Theo K Bammler; James MacDonald; Leo J Pallanck (PLoS Genetics)
Mutations in GBA (glucosylceramidase beta), which encodes the lysosomal enzyme glucocerebrosidase (GCase), are the strongest genetic risk factor for the neurodegenerative disorders Parkinson's disease (PD) and Lewy body dementia. Recent work has suggested that neuroinflammation may be an important factor in the risk conferred by GBA mutations. We therefore systematically tested the contributions of immune-related genes to neuropathology in a Drosophila model of GCase deficiency. We identified target immune factors via RNA-Seq and proteomics on heads from GCase-deficient flies, which revealed both increased abundance of humoral factors and increased macrophage activation. We then manipulated the identified immune factors and measured their effect on head protein aggregates, a hallmark of neurodegenerative disease. Genetic ablation of humoral (secreted) immune factors did not suppress the development of protein aggregation. By contrast, re-expressing Gba1b in activated macrophages suppressed head protein aggregation in Gba1b mutants and rescued their lifespan and behavioral deficits. Moreover, reducing the GCase substrate glucosylceramide in activated macrophages also ameliorated Gba1b mutant phenotypes. Taken together, our findings show that glucosylceramide accumulation due to GCase deficiency leads to macrophage activation, which in turn promotes the development of neuropathology.